2021
DOI: 10.1155/2021/8254344
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ashwagandha Root Extract on Cognitive Functions in Healthy, Stressed Adults: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Background. The global prevalence of stress is increasing. Stress adversely affects cognitive ability, sleep quality, and overall psychological well-being. Ashwagandha (Withania somnifera (L.) Dunal), an essential medicine in Ayurveda, is reportedly beneficial in reducing stress and improving memory. This double-blind, randomized, placebo-controlled clinical study evaluated the effect of Ashwagandha root extract sustained-release capsule 300 mg (Prolanza™; hereafter Ashwagandha SR) on cognitive functions, stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…Although the current study was conducted in tissue culture in rat embryonic hippocampal neurons, the results reported herein nevertheless provide a plausible molecular mechanism underlying recent clinical findings that WS improves psychological and cognitive effects in depressed patients [26,37,38] possibly through the hypothalamus-adrenal-pituitary axis [29]. Moreover, Manchanda and Kaur [39] have reported that hippocampal BDNF mRNA and phospho-Akt was increased in rats fed WS leaf extracts, relative to those fed a low-fat diet, albeit not statistically so.…”
Section: Discussionmentioning
confidence: 89%
“…Although the current study was conducted in tissue culture in rat embryonic hippocampal neurons, the results reported herein nevertheless provide a plausible molecular mechanism underlying recent clinical findings that WS improves psychological and cognitive effects in depressed patients [26,37,38] possibly through the hypothalamus-adrenal-pituitary axis [29]. Moreover, Manchanda and Kaur [39] have reported that hippocampal BDNF mRNA and phospho-Akt was increased in rats fed WS leaf extracts, relative to those fed a low-fat diet, albeit not statistically so.…”
Section: Discussionmentioning
confidence: 89%
“…Subiektywną poprawę jakości snu wśród osób zdrowych odnotowano w badaniu nad wpływem W. somnifera na funkcje kognitywne u zdrowych, zestresowanych ludzi [17]. Proporcjonalność poprawy subiektywnej oceny jakości snu wraz z zwiększającą się dawką preparatu została opisana w jednym randomizowanym, przeprowadzonym metodą podwójnie ślepej próby badaniu porównawczym przeprowadzonym przez Salve J et al (2019) [18].…”
Section: Badania Na Ludziachunclassified
“…The extract of this drugs induce the dendrites and axon outgrowth and its show the neuronal regeneration. 10…”
Section: Chemical Compositionsmentioning
confidence: 99%